Construção de textos colaborativos: utilização da ferramenta Trello para o desenvolvimento de artigo científico na 3ª série do ensino médio - Silva, Cíntya Jíminni Brito da (2022)
Thinking about education is to enable ways for learning to happen. The school environment should be the space in which actions in favor of knowledge take place in a democratic way. For this, it is necessary to have a break with the traditional teaching format and that innovative and educational experiences are practices that help in the student's training process. To expand this knowledge, the use of new resources, including digital technology, provide opportunities for the development of new skills in the teaching-learning process, both for the teacher who assumes the role of mediator, and for the student who is the protagonist of his story. Our study was developed in the context of the use of digital technological resources in Portuguese language classes, stimulating teachers and students to practice digital literacy. To carry out our study, we used the technological tool Trello, which is in the field of Contemporary Technologies and Teaching. The general objective of our work was to investigate how the Trello tool was used for the construction of the scientific article in a collaborative way by 3rd grade high school students. As a theoretical contribution, we resort to the precepts of Lévy (2010), Kensky (2014) and Moran (2018) with regard to technology and Education; koch (2003) and Xavier (2010) in the lines of text and hypertext, as well as Araújo (2009), Santaella (2014), Ribeiro (2017), Coscarelli (2017), Buzato (2001) to practices for digital literacy. Rojo (2005), Soares (2002), Kleiman (2005) and Bazerman (2007) for conducting the literacy process, Leffa (2006) and Mattos (2020) for new digital learning resources, among others. The study was developed with 3rd grade students’ high school and a Portuguese language teacher at a State Technical School located in the city of Recife-Pe. The qualitative and quantitative investigation was based on the interpretive approach, by Bortoni-Ricardo (2019) and quantitative under the eyes of Creswell (2021), Lakatos and Marconi (2003). As methodological procedures, we investigated the use of the Trello tool for the construction of the scientific article textual genre in a collaborative way in which we followed the stages of the textual production of two groups A and B. For data collection and analysis, we applied two questionnaires through the Google form. One for the two groups of students, containing 10 objective questions, and the other for the teacher, with 8 objective questions. Among the results of the study, we verified: the collaborative functionality and the adaptation of the Trello Tool as a pedagogical resource used by the students and the teacher; the construction of scientific articles by the participating students, who were able to visualize and understand the process of scientific writing in a sequential and collaborative way, and, finally, perception and functionality of the Trello tool as a support for the development process of digital literacy.